Monoamine oxidase activity in placenta in relation to manganese, cadmium, lead, and mercury at delivery - Abdelouahab, Nadia; Huel, Guy; Suvorov, Alexander; Foliguet, Bernard; Goua, Valérie; Debotte, Ginette; Sahuquillo, Josianne; Charles, Marie-Aline; Takser, Larissa (Neurotoxicology and teratology, 2010)
Environmental prenatal exposure to potentially neurotoxic metals poses a particular challenge with regard to the study of early toxic effects. Monoamine oxidase activity, shown to be influenced by metals in experimental studies, could be a useful biomarker in humans. To examine the relationship between blood metal concentrations at delivery and placenta MAO activity. The study was performed in 163 pregnancies. Maternal and cord blood samples were obtained for manganese (Mn), lead (Pb), and cadmium (Cd) determination. Mercury (Hg) was also analysed in maternal hair. Placental samples were stored immediately after expulsion and total MAO activity was measured. MAO activity was significantly positively correlated with maternal and cord blood Mn concentrations in subjects with high MAO activity. In subjects with low MAO activity, maternal hair Hg was negatively correlated with MAO. Our results suggest the use of placental MAO as a potential surrogate marker of Mn toxicity in the newborn and its correlation with psychomotor development should be further investigated.